THERMODYNAMICS OF IRON OXIDES: PART III. ENTHALPIES OF FORMATION AND STABILITY OF FERRIHYDRITE (~FE(OH)3), SCHWERTMANNITE (~FEO(OH)3/4(SO4)1/8), AND ε-FE2O3 - Majzlan J.; Navrotsky A.; Schwertmann U. (My University, 2004)
Enthalpies of formation of ferrihydrite and schwertmannite were measured by acid solution calorimetry in 5 N HCl at 298 K. The published thermodynamic data for these two phases and ε-Fe2O3 were evaluated, and the best thermodynamic data for the studied compounds were selected.Ferrihydrite is metastable in enthalpy with respect to α-Fe2O3 and liquid water by 11.5 to 14.7 kJ•mol−1 at 298.15 K. The less positive enthalpy corresponds to 6-line ferrihydrite, and the higher one, indicating lesser stability, to 2-line ferrihydrite. In other words, ferrihydrite samples become more stable with increasing crystallinity. The best thermodynamic data set for ferrihydrite of composition Fe(OH)3 was selected by using the measured enthalpies and (1) requiring ferrihydrite to be metastable with respect to fine-grained lepidocrocite; (2) requiring ferrihydrite to have entropy higher than the entropy of hypothetical, well-crystalline Fe(OH)3; and (3) considering published estimates of solubility products of ferrihydrite. The ΔG°f for 2-line ferrihydrite is best described by a range of −708.5±2.0 to −705.2±2.0 kJ•mol−1, and ΔG°f for 6-line ferrihydrite by −711.0±2.0 to −708.5±2.0 kJ•mol−1.A published enthalpy measurement by acid calorimetry of ε-Fe2O3 was re-evaluated, arriving at ΔH°f (ε-Fe2O3) = −798.0±6.6 kJ•mol−1. The standard entropy (S°) of ε-Fe2O3 was considered to be equal to S° (γ-Fe2O3) (93.0±0.2 J•K−1•mol−1), giving ΔG°f (ε-Fe2O3) = −717.8±6.6 kJ•mol−1. ε-Fe2O3 thus appears to have no stability field, and it is metastable with respect to most phases in the Fe2O3-H2O system which is probably the reason why this phase is rare in nature.Enthalpies of formation of two schwertmannite samples are: ΔH°f (FeO(OH)0.686(SO4)0.157•0.972H2O) = −884.0±1.3 kJ•mol−1, ΔH°f (FeO(OH)0.664(SO4)0.168•1.226H2O) = −960.7±1.2 kJ•mol−1. When combined with an entropy estimate, these data give Gibbs free energies of formation of −761.3 ± 1.3 and −823.3 ± 1.2 kJ•mol−1 for the two samples, respectively. These ΔGf° values imply that schwertmannite is thermodynamically favored over ferrihydrite over a wide range of pH (2–8) when the system contains even small concentration of sulfate. The stability relations of the two investigated samples can be replicated by schwertmannite of the “ideal” composition FeO(OH)3/4(SO4)1/8 with ΔG°f = −518.0±2.0 kJ•mol−1.